Technical, economic, and social impact of photovoltaic at dormitory building - I Made Aditya Nugraha; I Gusti Made Ngurah Desnanjaya (Institute of Advanced Engineering and Science, 2022)
Marine and Fisheries Polytechnic of Kupang is one of the educational centers located in East Nusa Tenggara. The location of the campus is in an area with the potential for solar energy throughout the year and it is very possible to utilize this energy as a source of electrical energy. As a form of energy-saving and utilizing the existing potential in accordance with existing policy directions, this electrical energy potential will be utilized for 3 dormitories with a hybrid system with State Electricity Company. The utilization of renewable energy as a source of electrical energy can produce 44,294.20 kWh/year. The results of economic analyses are encouraging to intensify the use of such PV systems since the payback period is 8.79 years, and the internal rate of return is 9%. The results of the Spearman test of the relationship between technical, social, and economic gave a significant correlation (p<0.05). This shows that the use of photovoltaic PV systems on campus has a social and economic impact. The use of this renewable energy is expected to reduce the use of fossil energy which has a negative impact on the environment and assist government policies to support the use of renewable energy.